Surgical Management of Renal Cell Carcinoma with Inferior Vena Cava Thrombus: Experience from a Nepalese University Tertiary Care Center - Luitel, Bhojraj; Poudyal, Sujeet; Pradhan, Manish Man; Gnyawali, Diwas; Chapagain, Suman; Shrestha, Kajan Raj; Kansakar, Prasan Bir Singh; Shrestha, Uttam Krishna; Chalise, Pawan Raj (Grande Medical Journal, 2025)
Background An inferior vena cava (IVC) thrombus in Renal Cell Carcinoma (RCC) represents a challenging and complex scenario, requiring meticulous surgical planning and multidisciplinary care. We describe our experience in the surgical treatment of RCC with IVC thrombus extending to different levels of IVC and even reaching the right atrium. Method This is a retrospective observational study of patients who underwent surgery for RCC with IVC thrombus over 10 years from July 2014 to August 2024 in Tribhuvan University Teaching Hospital. Descriptive analysis assessed demographic characteristics, imaging, surgical treatment, and outcomes regarding complications and survival. Result A total of 35 RCC cases with IVC thrombus were retrospectively reviewed (mean age: 63.28 years; range: 35–75). Level II thrombus was most common (40%), while level IV was seen in six patients (17.14%). Of the level IV cases, four underwent cardiopulmonary bypass (CPB); in the remaining two, thrombus regression allowed clamping; one above and one just below the diaphragm. Among seven level III cases, two required supradiaphragmatic clamping, four were clamped between the diaphragm and hepatic veins, and one below the liver. In two cases with IVC wall invasion, segmental resection with end-to-end suturing was performed. High-grade (Clavien-Dindo IV–V) complications were noted in four level IV cases, with two perioperative deaths linked to CPB (pneumonia, pulmonary embolism). Clear cell carcinoma was the predominant subtype (94.29%), with papillary carcinoma in the remainder. Pathological nodal metastasis was present in 14.29%. Three-year overall survival was inversely related to thrombus level: 64.29% (level I), 62.5% (II), 57.14% (III), and 33.33% (IV). Distant metastasis, seen in 25.71%, was the leading cause of late mortality, particularly in node-positive cases. Conclusion The management of RCC with IVC thrombus is challenging, requiring meticulous surgical planning and multidisciplinary care. High-level IVC thrombus (Level III and IV) was associated with high perioperative morbidity and even mortality.